Detection of minimally disseminated disease in the cerebrospinal fluid of children with high-risk retinoblastoma by reverse transcriptase-polymerase chain reaction for GD2 synthase mRNA - Laurent, Viviana Eunice (2013)
Aim: To evaluate minimally disseminated disease (MDD) in cytologically negative cerebrospinal fluid (CSF) specimens of patients with high-risk retinoblastoma by the detection of the synthase of ganglioside GD2 mRNA by reverse transcriptase-polymerase chain reaction (RT-PCR). Methods: The CSF was evaluated in 26 patients with high risk for CSF relapse: 14 with postlaminar optic nerve invasion, five of them with tumour at the resection margin, five with massive choroidal invasion, three with overt orbital extension and four patients with systemic metastasis. Serial CSF examinations were repeated at different time intervals according to stage and in the event of suspected relapse. GD2 synthase mRNA was evaluated by RT and nested PCR at each procedure. Results: MDD was present at diagnosis in six cases (23%) and it was significantly associated to massive optic nerve involvement or history of glaucoma (p < 0.05). Three of the children with positive MDD had a CSF relapse. Thirteen patients had negative MDD at diagnosis and one had a CSF relapse. In seven children no ARN could be obtained for PCR analysis and two subsequently relapsed. The probability of CSF relapse was 0.50 (95% confidence interval (CI) 0.13–0.88) for children with MDD and 0.08 (95% CI 0.02–0.46) for those with negative RT-PCR examination of the CSF at diagnosis (p = 0.03). Conclusions: MDD in the CSF detected by RT-PCR for GD2-synthase mRNA occurred in 31.7% of evaluable high-risk children with retinoblastoma with no initial central nervous system (CNS) involvement. It was significantly associated to optic nerve involvement and glaucoma and increased risk of CSF relapse.